2020
DOI: 10.1016/j.artd.2020.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Similar Outcomes After Hospital-Based Same-Day Discharge vs Inpatient Total Hip Arthroplasty

Abstract: Background: There has been increasing interest in performing primary hip and knee replacement with same-day discharge (SDD). The purpose of this study is to compare patient-reported outcome (PRO) scores, pain scores, and readmissions in patients who underwent SDD total hip arthroplasty (THA) with those in patients who underwent traditional inpatient THA. Methods: A retrospective study was conducted on 963 patients who underwent primary THA at our institution between September 2016 and December 2018. Two cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…Regarding PROMs, we observed that patients undergoing fast-track THR in the study period experienced similar satisfaction and functional gains (Δ), as indicated by similar HOOS Jr and VR-12 scores from baseline scores. Our findings support previously published results of patients experiencing similar improvements in PROMs after early (e.g., ambulatory) discharge versus inpatient THR ( 27 , 28 ). Interestingly, in our study the preoperative PROMs trended towards being lower for the study cohort.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding PROMs, we observed that patients undergoing fast-track THR in the study period experienced similar satisfaction and functional gains (Δ), as indicated by similar HOOS Jr and VR-12 scores from baseline scores. Our findings support previously published results of patients experiencing similar improvements in PROMs after early (e.g., ambulatory) discharge versus inpatient THR ( 27 , 28 ). Interestingly, in our study the preoperative PROMs trended towards being lower for the study cohort.…”
Section: Discussionsupporting
confidence: 92%
“…Same day discharge arthroplasty is an established protocol which has been demonstrated to be safe with no significant increase in rates of complication or readmission, 24 - 27 nor has there been any decrease in patient reported outcomes. 28 There are evidence-based criteria to minimize the readmission and failures of SDS, and these were followed in the patient choices. 29 Assessments on cost-effectiveness and possible cost-reduction of day surgery procedures have also been favourable.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning decreased pain for the studies investigating a THA population, VAS scores between studies displayed results that were conflicting, with two studies favouring the inpatient group [ 52 , 54 ] while two studies favoured the outpatient group[ 57 , 58 ]. Timepoints of these assessments also varied, the results favouring the inpatient group were taken at time points less than three months after surgery, whereas the results favouring the outpatient group were assessed on the day of discharge and at a two-year follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Of those articles, 1,593 were removed as duplicates leaving 1829 to be reviewed at title and abstract level for eligibility. Following a second full-text screening of 55 articles, a final seven studies were included in this review [52][53][54][55][56][57][58]. The complete search and screening process is outlined in Fig.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%